Cleistocalyx nervosum var. paniala berry fruit protects neurotoxicity against endoplasmic reticulum stress-induced apoptosis. (May 2017) - Sukprasansap, Monruedee; Chanvorachote, Pithi; Tencomnao, Tewin
Abstract: Oxidative and endoplasmic reticulum (ER) stresses cause neuronal damage leading to neurodegenerative disorders. Cleistocalyx nervosum var. paniala (CNP) berry fruit has been shown to possess powerful antioxidant properties. Here, we investigated the neuroprotective effect of CNP extract against glutamate-mediated oxidative/ER stress-induced cell death in mouse hippocampal neuronal HT22 cells. CNP extract was clarified for its radical scavenging activities, total phenolic and anthocyanin contents. The key anthocyanin cyanidin-3-glucoside was used as a marker to standardize the extract used in the study. We found that pretreated cells with CNP extract (0.05–1 μg/ml) prevented neuronal cell death in response to 5 mM glutamate evaluated by cell viability MTT, LDH and apoptosis/necrosis Annexin V/propidium iodide co-staining assays. For mechanistic approach, glutamate-induced cell death through reactive oxygen species (ROS)-mediated ER stress pathways, indicating the increase of ROS and ER stress signature molecules including calpain, caspases-12 and C/EBP homologous proteins (CHOP). CNP extract inhibited ROS production. Moreover, the extract also suppressed the specific-ER stress apoptotic proteins level in glutamate-induced cells by upregulating the gene expression of cellular antioxidant enzymes (SODs, CAT, GPx and GSTs). Taken together, our results provide information about and the molecular mechanism of CNP extract as a promising neuroprotectant and antioxidant. Highlights: Cleistocalyx nervosum var. paniala (CNP) berry fruit contains important bioactive compound, especially anthocyanin. First report on CNP extract in protection of glutamate-induced oxidative/ER stress in HT22 cells. CNP extract exerts its antioxidant activities through its direct free radical scavenging property. CNP extract increases the cellular expression of antioxidant and phase II enzymes.